Work–family conflict and neck and back pain in surgical nurses. Issue 1 (2nd January 2018) - Baur, Heiner; Grebner, Simone; Blasimann, Angela; Hirschmüller, Anja; Kubosch, Eva Johanna; Elfering, Achim
Abstract : Objective . Surgical nurses' work is physically and mentally demanding, possibly leading to work–family conflict (WFC). The current study tests WFC to be a risk factor for neck and lower back pain (LBP). Job influence and social support are tested as resources that could buffer the detrimental impact of WFC. Methods . Forty-eight surgical nurses from two university hospitals in Germany and Switzerland were recruited. WFC was assessed with the Work–Family Conflict Scale. Job influence and social support were assessed with the Copenhagen Psychosocial Questionnaire, and back pain was assessed with the North American Spine Society Instrument. Results . Multiple linear regression analyses confirmed WFC as a significant predictor of cervical pain ( β  = 0.45, p  < 0.001) and LBP ( β  = 0.33, p  = 0.012). Job influence and social support did not turn out to be significant predictors and were not found to buffer the impact of WFC in moderator analyses. Conclusion . WFC is likely to affect neck and back pain in surgery nurses. Work–life interventions may have the potential to reduce WFC in surgery nurses.